Self-leveling anti-dispersion underwater bottom sealing material and preparation method thereof

By using a flocculant prepared by cross-linking reaction in the underwater back cover material, combined with components such as sulfoaluminate cement, the problem of difficulty in taking into account the underwater resistance to dispersion, self-leveling and high strength in the prior art is solved, and better flocculation effect and construction performance are achieved.

CN119528527AActive Publication Date: 2025-02-28SHIJIAZHUANG TIEDAO UNIV +2

Patent Information

Application Number
CN202510093148.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-02-28
Estimated Expiration
2045-01-21

AI Technical Summary

Technical Problem

The existing underwater non-dispersed concrete is difficult to take into account the underwater resistance to dispersion, self-leveling and high-strength properties.

Method used

A self-leveling anti-dispersed underwater back cover material is used, and its components include sulfur aluminate cement, ordinary silicate cement, fly ash, fine aggregate, water, water reducer, flocculant, retarder, defoaming agent and premature strength agent. The flocculant is prepared by cross-linking reaction of acrylamide and acrylic acid, which has the effect of improving adhesion and reducing water absorption.

Benefits of technology

The flocculant of this material can better bond with unhydrated particles, improve the coating force, enhance the flocculation effect, improve the fluidity and compressive strength of the material, and meet the multiple performance requirements of underwater bottom cover construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528527A_ABST
    Figure CN119528527A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of underwater construction materials, and particularly relates to a self-leveling anti-dispersion underwater bottom sealing material and a preparation method thereof. The self-leveling anti-dispersion underwater bottom sealing material disclosed by the invention is prepared from the following components in parts by weight: 530 to 730 parts of sulphoaluminate cement, 77 to 277 parts of ordinary Portland cement, 84 to 126 parts of fly ash, 870 to 950 parts of fine aggregate, 250 to 278 parts of water, 18 to 23 parts of a water reducing agent, 6 to 10 parts of a flocculating agent, 8 to 12 parts of a retarder, 0.9 to 1.4 parts of a de-foaming agent and 0.1 to 0.4 part of an early strength agent. The self-leveling dispersion-resistant underwater bottom sealing material disclosed by the invention has good fluidity and dispersion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of underwater construction materials, and in particular relates to a self-leveling anti-dispersion underwater bottom sealing material and a preparation method thereof. Background Art

[0002] Underwater bottom sealing material is an engineering material used in marine engineering and underwater construction environments. It is often used for sealing, protection and support of submarine tunnels, dams, bridges, etc. With the continuous advancement of engineering construction in my country, there are more diverse requirements for the performance of underwater bottom sealing materials. Underwater bottom sealing materials are generally required to have excellent underwater anti-dispersion properties to ensure the bonding and coating between cement slurry and aggregate in a dynamic water environment so that the material can fully play its role. It is also required to have good fluidity and self-leveling to facilitate underwater pouring construction. As a bottom sealing material, the strength development must be relatively rapid, and it can generate strength and play a structural role in a short time. When used in marine engineering or underwater environments with corrosive substances, the concrete is also required to have good density and corrosion resistance.

[0003] Concrete, steel, polymers, etc. can all be used as underwater bottom sealing materials, but concrete is suitable for most underwater bottom sealing projects due to its own advantages such as high strength, corrosion resistance, and simple and convenient construction process.

[0004] Underwater non-dispersible concrete is a special concrete added with anti-dispersant. It is generally required to keep the cement paste and aggregate wrapped together during underwater pouring, without dispersion and segregation, so as to ensure the development of concrete strength. At the same time, underwater non-dispersible concrete generally has high fluidity and can be self-leveling and self-compacting without vibration in underwater construction environment. However, when the existing underwater non-dispersible concrete is used in underwater bottom sealing construction, it is difficult to take into account the factors of underwater anti-dispersion, self-leveling and high strength.

[0005] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention

[0006] The object of the present invention is to provide a self-leveling anti-dispersion underwater bottom sealing material and a preparation method thereof, so as to help improve the performance of the underwater bottom sealing material.

[0007] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a self-leveling anti-dispersion underwater bottom sealing material, the underwater bottom sealing material comprising the following components in parts by weight: 530-730 parts of sulphoaluminate cement, 77-277 parts of ordinary Portland cement, 84-126 parts of fly ash, 870-950 parts of fine aggregate, 250-278 parts of water, 18-23 parts of water reducer, 6-10 parts of flocculant, 8-12 parts of retarder, 0.9-1.4 parts of defoamer and 0.1-0.4 parts of early strength agent; the flocculant is prepared by a method comprising the following steps: (1) uniformly mixing acrylamide solution, acrylic acid and a cross-linking agent and then dropping an initiator ; (2) stirring and reacting at 60°C to 80°C for 120 to 140 minutes to obtain a polyacrylamide hydrogel; (3) drying and crushing the polyacrylamide hydrogel; (4) dissolving the polyacrylamide hydrogel obtained by the treatment in step (3) in water to obtain a polyacrylamide hydrogel solution, and adjusting the pH of the polyacrylamide hydrogel solution to 8 to 11; (5) mixing the polyacrylamide hydrogel solution obtained by the treatment in step (4) with a hydroxyethyl methacrylate solution, adding an activator dropwise, stirring and reacting at 40°C to 60°C for 60 to 100 minutes, and then standing. After standing, the obtained product is decontaminated, dried and crushed to obtain the flocculant.

[0008] Preferably, in step (1), the molar ratio of acrylamide to acrylic acid is 2.2-3.6; in step (5), the mass ratio of polyacrylamide hydrogel to hydroxyethyl methacrylate is 0.8-1.2; and the concentration of the polyacrylamide hydrogel solution and / or the hydroxyethyl methacrylate solution is 3wt%-5wt%.

[0009] Preferably, in step (1), the cross-linking agent is N,N'-methylenebisacrylamide and / or ethylene glycol dimethacrylate, and the initiator is ammonium persulfate; the amount of the cross-linking agent is 0.04wt%~0.06wt% of the acrylamide; the amount of the initiator is 0.5wt%~0.6wt% of the acrylamide; and the concentration of the acrylamide solution is 25wt%~29wt%.

[0010] Preferably, in step (5), the standing time is 120 to 160 minutes.

[0011] Preferably, in step (5), the activator is a sodium carbonate solution, and the concentration of the sodium carbonate solution is 0.5 mol / L; the amount of the activator is 55 wt% to 65 wt% of methyl methyl hydroxyacrylate.

[0012] Preferably, the sulphoaluminate cement is a fast-hardening sulphoaluminate cement with a strength grade of 42.5 or above and a specific surface area of ​​350 mm or more. 2The fine aggregate is river sand with a fineness modulus of 1.8 to 2.2, a mud content of ≤1%, and a particle size of 0.15 mm to 2.36 mm; the fly ash is primary fly ash or secondary fly ash; the water reducer is a polycarboxylic acid water reducer with a water reduction rate of ≥25%; the early strength agent is lithium carbonate.

[0013] Preferably, the retarder is a mixture of sodium gluconate, sodium citrate and borax, and the mass ratio of sodium gluconate, sodium citrate and borax is (1.5-2.0):(4.2-4.7):(1.5-2.0).

[0014] Preferably, the total amount of the sulphoaluminate cement and ordinary Portland cement is 810 parts, and the mass ratio of the sulphoaluminate cement to ordinary Portland cement is 7:3-9:1.

[0015] The present invention also provides a method for preparing the self-leveling anti-dispersion underwater bottom sealing material as described above, which adopts the following technical scheme: the method for preparing the self-leveling anti-dispersion underwater bottom sealing material as described above comprises the following steps: I. adding sulphoaluminate cement, ordinary silicate cement, fly ash and flocculant into a mixer, dry mixing to obtain a dry mix; II. dissolving the retarder and the water reducer in at least part of the water, then adding them into the mixer and stirring; III. adding fine aggregate into the mixer and stirring; IV. dissolving the defoamer and the early strength agent in the remaining water, adding them into the mixer and stirring evenly to obtain the self-leveling anti-dispersion underwater bottom sealing material.

[0016] Beneficial effects: The flocculant in the self-leveling anti-dispersion underwater bottom sealing material of the present invention can better bond with the unhydrated particles, generate a greater coating force, and have a better flocculation effect.

[0017] The flocculant in the self-leveling anti-dispersion underwater bottom sealing material of the present invention adopts acrylamide and acrylic acid as monomers during the preparation process, and adds a cross-linking agent, which appropriately increases the amount of the cross-linking agent, greatly improves the cross-linking density of polyacrylamide, makes the network structure of polyacrylamide more compact, can reduce the entry of water molecules, and thus helps to reduce water absorption; the present invention also performs hydroxymethylation modification on the polyacrylamide hydrogel, introduces hydrophilic hydroxyl groups into the polyacrylamide molecular chain, and the hydroxyl groups can be directionally adsorbed on the surface of cement particles to form a water film with a lubricating effect. At the same time, the cement particles are dispersed from each other through the electrostatic repulsion between negative charges, so as to achieve the effect of improving the fluidity of the slurry and reducing water, and helps to solve the problem that the conventionally used polyacrylamide flocculant has a large water absorption amount, resulting in poor workability of cement-based materials.

[0018] The hydroxyl group of the flocculant in the self-leveling anti-dispersion underwater bottom sealing material of the present invention has good adaptability to the polycarboxylate water-reducing agent, can maintain the uniformity of the mixture when mixing cement slurry, and has good fluidity while ensuring the flocculation effect.

[0019] The self-leveling anti-dispersion underwater bottom sealing material of the present invention uses sulphoaluminate cement, ordinary Portland cement and fly ash as cementitious materials. The sulphoaluminate cement has a fast setting and hardening speed and has a very high early strength, which can ensure that the concrete cast in the underwater bottom sealing construction has sufficient strength in a short time. The sulphoaluminate cement also has a micro-expansion characteristic, which can avoid the shrinkage caused by the use of ordinary cement in the underwater bottom sealing construction, making the structure more compact. When applied to submarine projects or corrosive ion water environments, the concrete cast with ordinary cement has better corrosion resistance and better durability. The addition of a certain amount of ordinary Portland cement can adjust the too short setting time of the sulphoaluminate cement and can also ensure that the mid- and late-stage strength can continue to develop. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them: Figure 1 The graph is a test result of the setting time and compressive strength of the underwater bottom sealing material of Examples 1, 2, 3 and Comparative Example 5; Figure 2 It is a graph showing the cement loss test results of the self-leveling anti-dispersion underwater backing material of Examples 1, 4, 5 and 6; Figure 3 The graphs are the test results of setting time and compressive strength of underwater bottom sealing materials of Example 1 and Comparative Examples 1, 2, 3, 4, 11, 12 and 13; Figure 4 The suspended matter content and fluidity test results of the underwater bottom sealing materials of Example 1 and Comparative Examples 6, 7, 8, 9 and 10 are shown in FIG. Figure 5 This is a test diagram of the fluidity of the self-leveling anti-dispersion underwater backing material prepared in Example 1 (the test is performed after the stirring in step S4 is completed); Figure 6 This is a fluidity test chart of the self-leveling anti-dispersion underwater backing material prepared in Example 1 (after the stirring in step S4 is completed, it is first covered with a wet cloth and allowed to stand for 30 minutes, and then stirred again to test the fluidity). DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0022] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0023] Aiming at the problem that the current underwater bottom sealing materials are difficult to achieve underwater anti-dispersion, self-leveling and high strength, the present invention provides a self-leveling anti-dispersion underwater bottom sealing material to help improve the performance of the underwater bottom sealing material.

[0024] The self-leveling anti-dispersion underwater bottom sealing material of the embodiment of the present invention includes the following components in parts by weight: 530-730 parts (for example, 530 parts, 560 parts, 590 parts, 710 parts or 730 parts) of sulphoaluminate cement, 77-277 parts (for example, 77 parts, 110 parts, 150 parts, 190 parts, 230 parts or 277 parts) of ordinary Portland cement, 84-126 parts (for example, 84 parts, 90 parts, 100 parts, 110 parts, 120 parts or 126 parts) of fly ash, 870-950 parts (for example, 870 parts, 890 parts, 910 parts, 930 parts or 950 parts) of fine aggregate, 250-278 parts (for example, 255 parts, 260 parts, 265 parts, 270 parts, 275 parts or 278 parts) of water, and 18-23 parts (for example, 18 parts, 1 9 parts, 20 parts, 21 parts, 22 parts or 23 parts), 6-10 parts (for example, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts) of flocculant, 8-12 parts (for example, 8 parts, 9 parts, 10 parts, 11 parts or 12 parts) of retarder, 0.9-1.4 parts (for example, 0.9 parts, 1 parts, 1.1 parts, 1.2 parts, 1.3 parts or 1.4 parts) of defoamer and 0.1-0.4 parts (for example, 0.1 parts, 0.2 parts, 0.3 parts or 0.4 parts) of early strength agent; the flocculant is prepared by a method comprising the following steps: (1) uniformly mixing acrylamide solution, acrylic acid and a cross-linking agent, and then dropping an initiator; (2) stirring and reacting at 60°C-80°C (for example, 60°C, 65°C, 70°C, 75°C or 80°C) for 120-140 min (for example, 120 min, 125 min, 130 min, 135 min or 140 min), to obtain a polyacrylamide hydrogel; (3) drying and crushing the polyacrylamide hydrogel; (4) dissolving the polyacrylamide hydrogel obtained by the treatment in step (3) in water to obtain a polyacrylamide hydrogel solution, and adjusting the pH of the polyacrylamide hydrogel solution to 8-11 (for example, 8, 9, 10 or 11); (5) mixing the polyacrylamide hydrogel solution obtained by the treatment in step (4) with a hydroxyethyl methacrylate solution, dropping an activator, stirring and reacting at 40°C-60°C (for example, 40°C, 45°C, 50°C, 55°C or 60°C) for 60-100 min (for example, 60 min, 70 min, 80 min, 90 min or 100 min), and then standing. After standing, the obtained product is impurity-removed, dried and crushed to obtain a flocculant.In step (2), if the reaction temperature is too low or the reaction time is too short, the reaction will not be fully carried out, the reactants will not be fully utilized and less products will be generated; too high a reaction temperature will destroy the reaction monomers and polymer molecular chains; a longer reaction time has little effect on the product, but it is not necessary from the perspective of preparation efficiency; step (4) the polyacrylamide hydrogel solution is adjusted to a pH suitable for the subsequent hydroxymethylation reaction; in step (5), if the reaction temperature is too low or the time is too short, the reaction will be incomplete; if the reaction temperature is too high, the structure will be destroyed; the hydroxymethylation modification in step (5) is carried out after the polyacrylamide hydrogel is prepared, which helps to avoid the situation where the products generated by placing multiple reactants in the same reaction system are difficult to control; the activator in step (5) helps to reduce the energy required for the reaction, increase the reaction rate, and thus promote the hydroxymethylation reaction; step (5) introduces hydroxymethyl groups through hydroxymethylation modification, which helps to further improve the hydrophilicity of the flocculant.

[0025] In a preferred embodiment of the self-leveling anti-dispersion underwater backing material of the present invention, in step (1), the molar ratio of acrylamide to acrylic acid is 2.2-3.6 (for example, 2.2, 2.5, 2.8, 3.1, 3.4 or 3.6); in step (5), the concentration of the polyacrylamide hydrogel solution and / or the hydroxyethyl methacrylate solution is 3wt%-5wt% (for example, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%). Among them, the molar ratio of acrylamide to acrylic acid has a great influence on the flocculation effect of the synthesized polyacrylamide; the molar ratio of acrylamide to acrylic acid is 2.2-3.6, which is the most suitable ratio range. If it is too high or too low, the flocculation effect will be greatly reduced.

[0026] Preferably, the mass ratio of hydroxyethyl methacrylate to polyacrylamide hydrogel is 0.8-1.2 (e.g., 0.8, 0.9, 1.0, 1.1 or 1.2). If the usage ratio of polyacrylamide hydrogel to hydroxyethyl methacrylate is too high or too low, one of the raw materials will have too much residue, which is not conducive to subsequent purification.

[0027] In a preferred embodiment of the self-leveling anti-dispersion underwater backing material of the present invention, in step (1), the crosslinking agent is N,N'-methylenebisacrylamide and / or ethylene glycol dimethacrylate, and the initiator is ammonium persulfate; the concentration of the acrylamide solution is 25wt%~29wt%; the amount of the crosslinking agent is 0.04wt%~0.06wt% of the acrylamide, and the amount of the initiator is 0.5wt%~0.6wt% of the acrylamide. Among them, the conventional amount of the crosslinking agent is 0.02wt%. The present invention helps to increase the crosslinking density of polyacrylamide by increasing the amount of the crosslinking agent, making the network structure of the polyacrylamide more compact, which can reduce the entry of water molecules, and thus helps to reduce water absorption.

[0028] In a preferred embodiment of the self-leveling anti-dispersion underwater backing material of the present invention, in step (5), the standing time is 120 to 160 minutes (for example, 120 minutes, 130 minutes, 140 minutes, 150 minutes or 160 minutes). If the standing time is too short, the reaction cannot be fully carried out.

[0029] In a preferred embodiment of the self-leveling anti-dispersion underwater backing material of the present invention, in step (5), the obtained product is extracted with acetone to remove impurities. The purpose of acetone extraction is to purify and remove impurities, and the main impurities are the unreacted parts of the above reactants. Preferably, the acetone extraction time is 3 hours, and after the standing is completed, acetone is added to the obtained product and mixed and stirred for 3 hours, and then the acetone is removed; wherein, acetone is volatile, and N2 can be introduced after the acetone extraction is completed to remove the acetone vapor.

[0030] In a preferred embodiment of the self-leveling anti-dispersion underwater backing material of the present invention, in step (5), the activator is a sodium carbonate solution, and the concentration of the sodium carbonate solution is 0.5 mol / L; the amount of the activator is 55wt%~65wt% of hydroxyethyl methacrylate (for example, 55wt%, 57wt%, 59wt%, 61wt%, 63wt% or 65wt%).

[0031] In a preferred embodiment of the self-leveling anti-dispersion underwater bottom sealing material of the present invention, the total amount of sulphoaluminate cement and ordinary Portland cement is 810 parts, and the mass ratio of sulphoaluminate cement to ordinary Portland cement is 7:3~9:1 (for example, 7:3, 8:2 or 9:1).

[0032] In a preferred embodiment of the self-leveling anti-dispersion underwater backing material of the present invention, the sulphoaluminate cement is a fast-hardening sulphoaluminate cement with a strength grade of 42.5 or above and a specific surface area of ​​350 m 2 / g fine aggregate is river sand with fineness modulus 1.8~2.2, mud content ≤1%, and particle size 0.15mm~2.36mm; fly ash is first-grade fly ash or second-grade fly ash; water reducer is polycarboxylic acid water reducer with water reduction rate ≥25%; early strength agent is lithium carbonate.

[0033] In a preferred embodiment of the self-leveling anti-dispersion underwater backing material of the present invention, the retarder is a mixture of sodium gluconate, sodium citrate and borax, and the mass ratio of sodium gluconate, sodium citrate and borax is (1.5-2.0):(4.2-4.7):(1.5-2.0) (for example, 1.5:4.2:1.5, 1.5:4.5:1.5, 1.5:4.7:1.5, 2.0:4.2:1.5, 1.8:4.2:1.5, 2.0:4.2:2.0, 1.8:4.5:1.8, 2.0:4.2:1.8 or 1.8:4.7:2.0, etc.). Among them, sodium gluconate is a large molecule with the best retarding effect, but too much of it will cause water exudation into the slurry; the addition of sodium citrate can improve the fluidity of the slurry and slightly increase the compressive strength; too much borax will lead to a decrease in compressive strength, and adding an appropriate amount can improve the early strength.

[0034] The present invention also proposes a method for preparing the self-leveling anti-dispersion underwater bottom sealing material as described above. The method for preparing the self-leveling anti-dispersion underwater bottom sealing material of the embodiment of the present invention comprises the following steps: I. adding sulphoaluminate cement, ordinary silicate cement, fly ash and flocculant into a mixer, dry mixing to obtain a dry mix; II. dissolving a retarder and a water reducer in at least part of the water, then adding them into the mixer and stirring; III. adding fine aggregate into the mixer and stirring; IV. dissolving a defoamer and an accelerator in the remaining water, adding them into the mixer and stirring evenly to obtain the anti-dispersion underwater bottom sealing material.

[0035] The flocculant that can be used for underwater bottom sealing materials, the anti-dispersion underwater bottom sealing material and the preparation method thereof of the present invention are described in detail below through specific embodiments.

[0036] In the following embodiments: The sulphoaluminate cement was R∙SAC 42.5 grade rapid hardening sulphoaluminate cement (Henan Dengdian Group Cement Co., Ltd.), with a specific surface area of ​​409m 2 / g initial setting time is 5min, final setting time is 8min, and 1d strength is 32MPa; ordinary cement is P∙O.42.5 grade ordinary Portland cement; fly ash is secondary fly ash; fine aggregate is continuously graded river sand with a fineness modulus of 1.9 and a maximum particle size of 1.18mm; the water reducer is a standard polycarboxylic acid high-performance water reducer with a water reduction rate of 25%; the defoamer uses a polyether defoamer (JQ-901 polyether defoamer produced by Jingqi Chemical Technology Co., Ltd.).

[0037] Example 1 The self-leveling anti-dispersion underwater bottom sealing material of this embodiment includes the following components in parts by weight: 648 parts of sulphoaluminate water, 162 parts of ordinary Portland cement, 90 parts of fly ash, 900 parts of fine aggregate, 270 parts of water, 22.5 parts of water reducer, 9 parts of flocculant, 8.1 parts of retarder (including 1.8 parts of sodium gluconate, 4.5 parts of sodium citrate and 1.8 parts of borax), 1.35 parts of defoamer and 0.27 parts of lithium carbonate.

[0038] Wherein, the flocculant is prepared by a method comprising the following steps: (1) dissolving 15 parts of acrylamide in 40 parts of distilled water to obtain an acrylamide solution; (2) Add the prepared acrylamide solution into a three-necked flask, followed by 5 parts of acrylic acid and 0.006 parts of cross-linking agent ethylene glycol dimethacrylate; (3) Add 0.075 parts of ammonium persulfate initiator dropwise from one of the three-necked flasks. (4) Stirring at 60°C in a constant temperature magnetic stirrer for 120 min to obtain polyacrylamide hydrogel; (5) Take out the product, dry it in a vacuum drying oven for 5 hours, and then crush it into small particles with a particle size less than 100 mesh (can pass through a 100 mesh sieve); (6) Dissolve 5 parts of the polyacrylamide obtained by the reaction in 95 parts of water to prepare a solution with a concentration of 5%, adjust the pH to 8 with 1 mol / L NaOH, and add 5 parts of hydroxyethyl methacrylate and 95 parts of water to another beaker to prepare an equal amount of hydroxyethyl methacrylate with a concentration of 5%; (7) Pour the two solutions into a three-necked flask, add 3 parts of activator (the activator is 0.05 mol / L sodium carbonate solution), stir at a constant temperature of 50°C in a constant temperature magnetic stirrer for 90 min, and then let it stand for 140 min; (8) The reaction product was extracted with acetone for 3 h, dried in a vacuum oven, and crushed again to obtain a hydroxymethylated polyacrylamide hydrogel (i.e., flocculant).

[0039] The method for preparing the self-leveling anti-dispersion underwater backing material of this embodiment comprises the following steps: S1. Add sulphoaluminate cement, ordinary Portland cement, fly ash and flocculant into a mixer and dry mix for 30 seconds; S2. Dissolve the retarder and water reducer in 70% water, add into the mixer and stir for 1 min; S3. Add aggregate and continue stirring for 1 minute; S4. Dissolve the defoamer and early strength agent (lithium carbonate) in the remaining 30% of the water, add the mixture into a stirrer, and continue stirring for 2 minutes to obtain a uniform self-leveling anti-dispersion water-based backing material of this embodiment.

[0040] Example 2 The self-leveling anti-dispersion underwater bottom sealing material of this embodiment is different from that of Embodiment 1 only in that the amount of sulphoaluminate cement is 567 parts and the amount of ordinary Portland cement is 243 parts; the rest is consistent with that of Embodiment 1.

[0041] Example 3 The self-leveling anti-dispersion underwater bottom sealing material of this embodiment is different from that of Embodiment 1 only in that the amount of sulphoaluminate cement is 729 parts and the amount of ordinary Portland cement is 81 parts; the rest is consistent with that of Embodiment 1.

[0042] Example 4 The self-leveling anti-dispersion underwater bottom sealing material of this embodiment is different from that of Embodiment 1 only in that the amount of flocculant used is 6 parts; the rest is consistent with that of Embodiment 1.

[0043] Example 5 The self-leveling anti-dispersion underwater bottom sealing material of this embodiment is different from that of Embodiment 1 only in that the amount of flocculant used is 3 parts; the rest is consistent with that of Embodiment 1.

[0044] Example 6 The self-leveling anti-dispersion underwater bottom sealing material of this embodiment is different from that of Embodiment 1 only in that the amount of flocculant used is 12 parts; the rest is consistent with that of Embodiment 1.

[0045] Comparative Example 1 The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that the retarder is omitted; the rest is the same as that of Example 1.

[0046] Comparative Example 2 The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that the amount of borax used is increased from 1.8 parts to 4.5 parts; the rest is consistent with Example 1.

[0047] Comparative Example 3 The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that 4.5 parts of sodium citrate are replaced by 4.5 parts of sucrose; the rest is the same as that of Example 1.

[0048] Comparative Example 4 The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that the amount of sodium gluconate is increased from 1.8 parts to 4.5 parts; the rest is the same as that of Example 1.

[0049] Comparative Example 5 The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that the amount of sulphoaluminate cement is 810 parts and the amount of ordinary Portland cement is 0; the rest is consistent with Example 1.

[0050] Comparative Example 6 The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that commercially available polyacrylamide (molecular weight is the same as that of the flocculant in Example 1; anionic polyacrylamide with a molecular weight of 12 million produced by Zhengzhou Chengyuan Environmental Protection Technology Co., Ltd.) is used to replace the flocculant in Example 1; the rest is consistent with Example 1.

[0051] Comparative Example 7 The flocculant used in the underwater backing material of this comparative example is prepared by a method comprising the following steps: (1) dissolving 20 parts of acrylamide in 40 parts of distilled water to obtain an acrylamide solution; (2) Add the prepared acrylamide solution into a three-necked flask, followed by 5 parts of acrylic acid and 0.006 parts of cross-linking agent ethylene glycol dimethacrylate; (3) Add 0.075 parts of ammonium persulfate initiator dropwise from one of the openings of the three-necked flask; (4) Stirring at 60°C in a constant temperature magnetic stirrer for 120 min to obtain polyacrylamide hydrogel; (5) Take out the product, dry it in a vacuum drying oven for 5 hours, and then crush it into small particles or powder of a specific particle size (can pass through a 100-mesh sieve) using a pulverizer; (6) Dissolve 5 parts of the polyacrylamide obtained by the reaction in 95 parts of water to prepare a solution with a concentration of 5%, adjust the pH to 8 with 1 mol / L NaOH, and add 5 parts of hydroxyethyl methacrylate and 95 parts of water to another beaker to prepare an equal amount of hydroxyethyl methacrylate with a concentration of 5%; (7) Pour the two solutions into a three-necked flask, add 3 parts of activator (the activator is 0.05 mol / L sodium carbonate solution), stir at a constant temperature of 50°C in a constant temperature magnetic stirrer for 90 min, and then let it stand for 140 min; (8) The reaction product was extracted with acetone for 3 h, then dried in a vacuum drying oven, and crushed again to obtain the flocculant of this comparative example. The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that the flocculant of Example 1 is replaced by the flocculant of this comparative example; the rest is the same as that of Example 1.

[0052] Comparative Example 8 The flocculant used in the underwater bottom sealing material of this comparative example is prepared by a method comprising the following steps: (1) dissolving 15 parts of acrylamide in 40 parts of distilled water to obtain an acrylamide solution; (2) Add the prepared acrylamide solution into a three-necked flask, and then add 5 parts of acrylic acid and 0.003 parts of cross-linking agent ethylene glycol dimethacrylate; (3) Add 0.075 parts of ammonium persulfate initiator dropwise from one of the openings of the three-necked flask; (4) Stirring at 60°C in a constant temperature magnetic stirrer for 120 min to obtain polyacrylamide hydrogel; (5) Take out the product, dry it in a vacuum drying oven for 5 hours, and then crush it into small particles or powder of a specific particle size (can pass through a 100-mesh sieve) using a pulverizer; (6) Dissolve 5 parts of the polyacrylamide obtained by the reaction in 95 parts of water to prepare a solution with a concentration of 5%, adjust the pH to 8 with 1 mol / L NaOH, and add 5 parts of hydroxyethyl methacrylate and 95 parts of water to another beaker to prepare an equal amount of hydroxyethyl methacrylate with a concentration of 5%; (7) Pour the two solutions into a three-necked flask, add 3 parts of activator (the activator is 0.05 mol / L sodium carbonate solution), stir at a constant temperature of 50°C in a constant temperature magnetic stirrer for 90 min, and then let it stand for 140 min; (8) The reaction product was extracted with acetone for 3 h, then dried in a vacuum drying oven, and pulverized again to obtain the flocculant of this comparative example.

[0053] The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that the flocculant of Example 1 is replaced by the flocculant of this comparative example; the rest is the same as that of Example 1.

[0054] Comparative Example 9 The flocculant that can be used for underwater bottom sealing material in this comparative example is prepared by a method comprising the following steps: (1) dissolving 15 parts of acrylamide in 40 parts of distilled water to obtain an acrylamide solution; (2) Add the prepared acrylamide solution into a three-necked flask, followed by 5 parts of acrylic acid and 0.006 parts of cross-linking agent ethylene glycol dimethacrylate; (3) Add 0.075 parts of ammonium persulfate initiator dropwise from one of the openings of the three-necked flask; (4) Stirring at 60°C in a constant temperature magnetic stirrer for 120 min to obtain polyacrylamide hydrogel; (5) The product was taken out and dried in a vacuum drying oven for 5 h, and then crushed into small particles of less than 100 mesh using a pulverizer (which can pass through a 100 mesh sieve), thereby obtaining the flocculant of this comparative example.

[0055] The anti-dispersion underwater bottom sealing material of this comparative example is different from that of Example 1 only in that the flocculant of Example 1 is replaced by the flocculant of this comparative example; the rest is the same as that of Example 1.

[0056] Comparative Example 10 The flocculant that can be used for underwater bottom sealing material in this comparative example is prepared by a method comprising the following steps: (1) dissolving 15 parts of acrylamide in 40 parts of distilled water to obtain an acrylamide solution; (2) Add the prepared acrylamide solution into a three-necked flask, followed by 5 parts of acrylic acid, 5% hydroxyethyl methacrylate solution (prepared from 5 parts of hydroxyethyl methacrylate and 95 parts of water) and 0.006 parts of cross-linking agent ethylene glycol dimethacrylate; (3) Add 0.075 parts of ammonium persulfate initiator and 3 parts of activator (the activator is 0.05 mol / L sodium carbonate solution) dropwise from one of the openings of the three-necked flask; (4) Stirring at 60°C in a constant temperature magnetic stirrer for 120 min to obtain polyacrylamide hydrogel; (5) The product was taken out and dried in a vacuum drying oven for 5 h, and then crushed into small particles or powder of a specific particle size (which can pass through a 100-mesh sieve) using a pulverizer to obtain the flocculant of this comparative example.

[0057] The underwater bottom sealing material of this comparative example is different from that of Example 1 only in that the flocculant of Example 1 is replaced by the flocculant of this comparative example; the rest is the same as that of Example 1.

[0058] Comparative Example 11 The difference between this comparative example and Example 1 is that 8.1 parts of sodium gluconate (sodium citrate and borax are omitted) are used as the retarder, and the rest are consistent with Example 1.

[0059] Comparative Example 12 The difference between this comparative example and Example 1 is that 8.1 parts of sodium citrate (sodium gluconate and borax are omitted) are used as the retarder, and the rest are consistent with Example 1.

[0060] Comparative Example 13 The difference between this comparative example and Example 1 is that 8.1 parts of borax (sodium gluconate and sodium citrate are omitted) are used as the retarder, and the rest are consistent with Example 1.

[0061] Experimental example According to GB / T1346-2011 "Test Method for Water Consistency, Setting Time and Stability of Cement Standard Consistency", GB / T50448-2015 "Technical Specification for Application of Cement-based Grouting Materials", GB / T17671-2021 "Test Method for Strength of Cement Mortar (ISO Method)" and DL / T5117-2021 "Test Procedure for Underwater Non-dispersible Concrete", the setting time, fluidity, compressive strength and underwater anti-dispersion performance of the underwater bottom sealing materials of the above embodiments and comparative examples were tested.

[0062] Test results such as Figure 1-6 As shown in Table 1 below: Table 1

[0063] Figure 1 The results of setting time and compressive strength test of Examples 1, 2, 3 and Comparative Example 5 are shown in the figure. The variable is the ratio of sulphoaluminate cement to ordinary Portland cement. As can be seen from the figure, the higher the relative content of sulphoaluminate cement, the shorter the setting time of the slurry, the greater the corresponding loss of fluidity over time, but the early compressive strength of the specimen will be relatively high. Considering the workability and strength, the ratio of sulphoaluminate cement to ordinary Portland cement is better when it is 8:2 or 7:3. In Example 1, a ratio of 8:2 is used, the initial setting time is 72 minutes, the final setting time is 101 minutes, and the initial fluidity is 320 mm (such as Figure 5 As shown), the fluidity after 30 minutes is 280mm (as shown Figure 6 As shown; the fluidity loss of the self-leveling anti-dispersion underwater bottom sealing material of Example 1 is small over time), the compressive strength of 1d can reach 44.26MPa, the 3d strength is 54.51MPa, and the 7d strength is 58.71MPa, which can meet the requirements of workability and strength during the construction process.

[0064] Figure 2 The test results of cement loss in Examples 1, 4, 5 and 6 are shown in Table 1. The variable is the amount of flocculant added. When the amount of flocculant added increases, the flocculation effect becomes significantly better, but when the amount of flocculant added is too low, the flocculation effect will not meet the requirements of underwater construction.

[0065] Figure 3The setting time and compressive strength test results of Example 1 and Comparative Examples 1, 2, 3, 4, 11, 12, and 13 are shown, and the variables are the type and proportion of the retarder. The addition of different amounts and types of retarders has a great influence on the working performance and mechanical properties of this underwater non-dispersible bottom sealing material. The compounding of the three retarders, sodium gluconate, sodium citrate, and boric acid, can produce a good retarding effect, and can extend the initial setting time from 9 minutes to more than 70 minutes, and the final setting time from 14 minutes to more than 100 minutes, which is beneficial to the construction of underwater bottom sealing projects. In contrast, the retarding effect of sugar is relatively poor; the retarder also has a good control effect on the time-dependent loss of fluidity of underwater bottom sealing materials. The initial fluidity of Example 1 reaches more than 300 mm, and the slurry fluidity after 30 minutes can be maintained at more than 280 mm, and the slurry fluidity is good.

[0066] Figure 4 The suspended matter content and fluidity test results of the embodiment and comparative examples 6, 7, 8, 9, and 10 are shown, and the variables are the types of flocculants used and some changes in the preparation process of the flocculants prepared by the present invention. It can be seen that the flocculant prepared by the present invention has good fluidity and underwater anti-dispersion performance compared with ordinary polyacrylamide; the amount of acrylamide in the monomer ratio is increased, but the raw material ratio and preparation process of the underwater anti-dispersion backing material remain consistent; the amount of cross-linking agent is reduced and the hydroxymethylation modification process is omitted. It can be seen that the prepared polyacrylamide is applied to the underwater backing material, which will significantly reduce its fluidity. This shows that the cross-linking agent modification and hydroxymethylation modification can produce the best water-reducing and anti-adsorption effect, and have a positive effect on the fluidity of the underwater backing material; the timing of adding hydroxyethyl methacrylate will affect the subsequent hydroxymethylation modification. Advancing the addition time will result in a reduction in the generated hydroxymethylation product and a poor water-reducing effect.

[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A self-leveling anti-dispersion underwater bottom sealing material, characterized in that: The underwater bottom sealing material comprises the following components in parts by weight: 530-730 parts of sulphoaluminate cement, 77-277 parts of ordinary Portland cement, 84-126 parts of fly ash, 870-950 parts of fine aggregate, 250-278 parts of water, 18-23 parts of water reducer, 6-10 parts of flocculant, 8-12 parts of retarder, 0.9-1.4 parts of defoamer and 0.1-0.4 parts of early strength agent; The flocculant is prepared by a method comprising the following steps: (1) After uniformly mixing acrylamide solution, acrylic acid and cross-linking agent, add initiator dropwise; (2) stirring and reacting at 60°C to 80°C for 120 to 140 minutes to obtain a polyacrylamide hydrogel; (3) drying and crushing the polyacrylamide hydrogel; (4) dissolving the polyacrylamide hydrogel obtained in step (3) in water to obtain a polyacrylamide hydrogel solution, and adjusting the pH of the polyacrylamide hydrogel solution to 8-11; (5) The polyacrylamide hydrogel solution obtained by the treatment in step (4) and the hydroxyethyl methacrylate solution are mixed, an activator is added dropwise, and the mixture is stirred at 40° C. to 60° C. for 60 to 100 minutes, and then allowed to stand. After the mixture is allowed to stand, the obtained product is decontaminated, dried and crushed to obtain the flocculant.

2. The self-leveling anti-dispersion underwater bottom sealing material according to claim 1, characterized in that: In step (1), the molar ratio of acrylamide to acrylic acid is 2.2 to 3.6; In step (5), the mass ratio of polyacrylamide hydrogel to hydroxyethyl methacrylate is 0.8-1.2; The concentration of the polyacrylamide hydrogel solution and / or the hydroxyethyl methacrylate solution is 3wt% to 5wt%.

3. The self-leveling anti-dispersion underwater bottom sealing material according to claim 1, characterized in that: In step (1), the crosslinking agent is N,N'-methylenebisacrylamide and / or ethylene glycol dimethacrylate, and the initiator is ammonium persulfate; The amount of the crosslinking agent is 0.04wt%~0.06wt% of the acrylamide; the amount of the initiator is 0.5wt%~0.6wt% of the acrylamide; The concentration of the acrylamide solution is 25wt%-29wt%.

4. The self-leveling anti-dispersion underwater bottom sealing material according to claim 1, characterized in that: In step (5), the standing time is 120 to 160 minutes.

5. The self-leveling anti-dispersion underwater bottom sealing material according to claim 1, characterized in that: In step (5), the activator is a sodium carbonate solution, and the concentration of the sodium carbonate solution is 0.5 mol / L; The amount of the activator used is 55wt% to 65wt% of methyl methacrylate.

6. The self-leveling anti-dispersion underwater bottom sealing material according to claim 1, characterized in that: The sulphoaluminate cement is a fast-hardening sulphoaluminate cement with a strength grade of 42.5 or above and a specific surface area of ​​350 mm or more. 2 ; The fine aggregate is river sand with a fineness modulus of 1.8 to 2.2, a mud content of ≤1%, and a particle size of 0.15 mm to 2.36 mm; The fly ash is primary fly ash or secondary fly ash; The water reducing agent is a polycarboxylate water reducing agent, and the water reducing rate is ≥25%; The early strength agent is lithium carbonate.

7. The self-leveling anti-dispersion underwater bottom sealing material according to claim 1, characterized in that: The retarder is a mixture of sodium gluconate, sodium citrate and borax, and the mass ratio of sodium gluconate, sodium citrate and borax is (1.5-2.0):(4.2-4.7):(1.5-2.0).

8. The self-leveling anti-dispersion underwater bottom sealing material according to claim 1, characterized in that: The total amount of the sulphoaluminate cement and ordinary Portland cement is 810 parts, and the mass ratio of the sulphoaluminate cement to ordinary Portland cement is 7:3-9:

1.

9. The method for preparing the self-leveling anti-dispersion underwater bottom sealing material according to any one of claims 1 to 8, characterized in that: The steps include: I. Add sulphoaluminate cement, ordinary Portland cement, fly ash and flocculant into a mixer and dry mix to obtain a dry mix; II. dissolving the retarder and the water reducer in at least a portion of the water, and then adding the retarder and the water reducer into the mixer and stirring; III. Add fine aggregate into the mixer and stir; IV. Dissolve the defoamer and early strength agent in the remaining water, add the mixture into the mixer, and stir evenly to obtain the self-leveling anti-dispersion underwater bottom sealing material.

Citation Information

Patent Citations

  • Polyacrylamide for oil well and preparation method of polyacrylamide

    CN110218278A

  • Underground non-dispersible grouting material for pile foundation repair and preparation method thereof

    CN113735525A

  • Salt-resistant water-non-dispersible cement paste and preparation method thereof

    CN117756448A

  • Concrete composite additive for crack resistance and preparation method thereof

    CN118930114A

Cited By

  • Preparation and application method of fly ash-based flow state curing material for offshore wind power fender pile

    CN120518364A